(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
OpenFAST is an open-source turbine simulation tool developed by the National Renewable Energy Laboratory (NREL). OpenFAST was originally developed for land-based wind turbines and later expanded to model fixed-bottom and floating wind turbines as well. It is a widely used tool within the wind energy industry and research community for turbine simulation, design, and loads analysis. Over the past few years, NREL researchers have been adding features and capabilities to OpenFAST to enable modeling of fixed and floating marine turbines. This development has focused on capturing additional physics relevant to operation in water and enabling the simulation of more diverse turbine geometries. Capabilities previously introduced for marine turbines include the inclusion of buoyant, added mass, and fluid inertia loads on the rotor, calculation of accelerations from the incoming current field, superposition of wave and current velocities, and a cavitation check to warn users if cavitation is occurring on a blade. OpenFAST development is also ongoing to enable modeling of multi-rotor systems, with multiple rotors attached to a single support structure. Additional work to further adapt OpenFAST for marine turbines was recently funded by the U.S. Department of Energy. Development for marine turbines is focused on capturing additional physics relevant to operation in water and enabling the simulation of more diverse support structure geometries. The work includes adding a flow confinement model for the rotor, a new dynamic stall model, rotor flow impacts from generalized support structures, cross-flow turbine controls, lifting loads on faired towers, and Keulegan-Carpenter (KC) number dependent platform drag forces. The final two additions are currently in development and will be discussed in more detail. Marine turbines can often take advantage of unidirectional or bidirectional inflow, with faired towers for reduced drag loads. These faired members physically introduce lift when there is some offset from the anticipated current direction, which could lead to important unexpected system loads. Lift force calculations on faired towers will be performed in the AeroDyn module following the same functions used for blade element lift forces. A separate input file option will allow users to define lift vs. angle of attack curves for the faired towers. This implementation will consider modification of the tower dam and tower shadow models, if necessary. Marine turbine support structures are subject to significant viscous drag loads with the inherent presence of current. Accurately capturing these loads is critical for mooring system and structural design. Drag coefficients in oscillatory flow are strongly dependent on KC number. Often, offshore wind support structure drag coefficients are changed depending on depth and sea state, accounting for changes in the KC number. The addition of current to wave and structure velocities further complicates the changes in drag between load cases. An option will be added to the HydroDyn module to have actively adjust drag coefficients as a function of the local instantaneous KC number.